Optimalisasi Terapi Antidiabetik Oral pada Diabetes Mellitus Tipe 2: Studi Komparatif Monoterapi dan Kombinasi terhadap Outcome Glikemik Optimalisasi Terapi Antidiabetik Oral pada Diabetes Mellitus Tipe 2: Studi Komparatif Monoterapi dan Kombinasi terhadap Outcome Glikemik - Kiki Rawitri; Sri Wahyuni; Syilvi Rinda Sari; Ziza Putri Aisyia Fauzi; Ferina Septiani Damanik; Cut Intan Annisa Puteri; Anggitha Ningtias (LPPM Universitas Abdurrab, 2026)
Type 2 diabetes mellitus (T2DM) is a chronic disease with a high prevalence in primary healthcare settings; however, real-world evidence regarding the effectiveness of oral antidiabetic therapies remains limited. This study aimed to compare the effectiveness of oral antidiabetic monotherapy and combination therapy in patients with T2DM at the Teladan Community Health Center (Puskesmas) in Medan. A non-experimental observational study with a cross-sectional design was conducted on 78 patients selected via systematic random sampling, utilizing medical records and data from the